2018
DOI: 10.1111/ppl.12828
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and proteomic approaches to explore the differences in monoterpene and benzenoid biosynthesis between scented and unscented genotypes of wintersweet

Abstract: Wintersweet (Chimonanthus praecox L.) is an important ornamental plant in China with a pleasant floral scent. To explore the potential mechanisms underlying differences in the fragrances among genotypes of this plant, we analyzed floral volatile organic compounds (VOCs) from two different genotypes: SW001, which has little to no fragrance, and the scented genotype H29. The major VOCs in H29 were linalool, trans-β-ocimene, benzyl acetate, methyl salicylate, benzyl alcohol (BAlc) and methyl benzoate. The most im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 79 publications
(106 reference statements)
0
26
0
Order By: Relevance
“…Terpene synthases (TPSs) are the enzymes responsible for the last catalytic reaction in the MVA and MEP pathway to generate terpenoid compounds. With the aid of the assembly genome, a total of 52 complete CpTPSs were identified (Additional file 1: Table S19), the number of which is approximately double that detected by transcriptomics in our previous study [5]. Phylogenetic analysis of TPS from four species revealed that CpTPSs were clustered into five of six subfamilies described for land plants (Fig.…”
Section: Evolution Of Terpene Biosynthesis and Regulation-related Genesmentioning
confidence: 92%
See 2 more Smart Citations
“…Terpene synthases (TPSs) are the enzymes responsible for the last catalytic reaction in the MVA and MEP pathway to generate terpenoid compounds. With the aid of the assembly genome, a total of 52 complete CpTPSs were identified (Additional file 1: Table S19), the number of which is approximately double that detected by transcriptomics in our previous study [5]. Phylogenetic analysis of TPS from four species revealed that CpTPSs were clustered into five of six subfamilies described for land plants (Fig.…”
Section: Evolution Of Terpene Biosynthesis and Regulation-related Genesmentioning
confidence: 92%
“…Monoterpenes are the major components of floral volatile organic compounds (VOCs) in wintersweet, especially the linalool, which accounts for more than half of the floral scent [5]. In plants, monoterpenes/diterpenes and sesquiterpenes are usually generated via the 2-C-methyl-D-erythritol 4-phosphate (MEP) pathway and the mevalonate (MVA) pathway, respectively [43].…”
Section: Evolution Of Terpene Biosynthesis and Regulation-related Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…() and Tian et al . () used RNA‐seq to try to pinpoint genes that are involved in flower volatile biosynthesis in Polianthes tuberosa , Freesia hybrida and wintersweet, respectively, that emit benzenoids and terpenoids, mostly terpenoids and terpenoids and benzenoids, respectively (Fan et al ., ; Huang et al ., ; Tian et al ., ). All three base their selection of gene candidates on homology and expression patterns.…”
Section: Voc Biosynthesismentioning
confidence: 99%
“…Tian et al () used an elegant combination of comparative transcriptomics and proteomics to explain the differences of VOC profiles between two genotypes of wintersweet, the fragrant H29 and the non‐fragrant SW001. The terpenoid and benzenoid profiles of the two genotypes differed widely.…”
mentioning
confidence: 99%